Pengaruh Independensi, Akuntabilitas Dan Due Professional Care Terhadap Kualitas Audit - Geri Gidion Wijaya; James Tumewu (LPPM Universitas Wijaya Kusuma Surabaya, 2024)
Audit quality is one of the services that is difficult to measure objectively, there is no definite definition of audit quality. This study aims to determine: (1) the effect of Independence on audit quality, (2) the effect of Accountability on audit quality, and (3) the effect of Due Professional care on audit quality. The sample of this research consisted of 15 Public Accounting Firms in Surabaya. Sampling was done by purposive sampling method. Data collection techniques in this study using a questionnaire (questionnaire). The type of data used in this study is primary data collected by sending questionnaires to respondents. The research method is quantitative, while the analysis technique uses Multiple Linear Regression Analysis. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression with the help of SPSS 20. The results of this study indicate that Independence and Due Professional Care have a significant effect on audit quality at the Surabaya Public Accounting Firm. Accountability is not effect on audit quality